2013
DOI: 10.1186/1472-6874-13-1
|View full text |Cite
|
Sign up to set email alerts
|

Care-seeking behavior of Japanese gynecological cancer survivors suffering from adverse effects

Abstract: BackgroundPost-treatment follow-up visits for gynecological cancer survivors should provide opportunities for management of adverse physical/psychological effects of therapy and early recurrence detection. However, the adequacy of such visits in Japan is poorly documented. We qualitatively explored care-seeking experiences of Japanese gynecological cancer survivors and deduced factors influencing care-seeking behaviors and treatment access.MethodsWe conducted 4 semi-structured focus groups comprising altogethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 34 publications
8
36
1
Order By: Relevance
“…This concurs with Holbrey and Coulson (2013) who found that participation in an online support group for women with PCOS can help women feel empowered, as it allows them to connect with other women with PCOS and enables them to access information and advice.…”
Section: Supportsupporting
confidence: 82%
See 1 more Smart Citation
“…This concurs with Holbrey and Coulson (2013) who found that participation in an online support group for women with PCOS can help women feel empowered, as it allows them to connect with other women with PCOS and enables them to access information and advice.…”
Section: Supportsupporting
confidence: 82%
“…To date, few studies have explored PCOS from a qualitative perspective (Crete and Adamshick, 2011; Holbrey and Coulson, 2013; Williams et al, 2014). Moreover, those studies excluded women with PCOS who experienced co-morbidities; Moreira and Azevedo (2006) argue that incorporating qualitative approaches into PCOS studies could contribute to our understanding of the impact of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In their study of 261 Barbadian females aged 15–19 years, Drakes et al (2013) found that one-third of their sample who were sexually active also self-reported from two to five or more sexual partners. Reliable data based on representative samples are lacking on whether these multiple sexual partners are concurrent, sequential, transactional, or affection-based relationships (Baumgartner et al, 2009).…”
Section: Intersectionality Theory and Researchmentioning
confidence: 99%
“…Therefore, age mixing may result from prevailing cultural patterns; incest, rape, and coercion; social pressures to acquiesce to elders or to men in authority; or from a combination of factors such as may be the case when school girls are offered money for school fees or gifts in exchange for sex (Allen et al, 2000; Gibbison, 2007), which is sometimes referred to as the “sugar daddy syndrome” (Drakes et al, 2013). It has also been reported that Jamaican youth aged 15–24 years, including students in tertiary institutions, are increasingly engaged in transactional and high-risk sexual practices with multiple partners for economic gain (Dunkley-Willis, 2014).…”
Section: Intersectionality Theory and Researchmentioning
confidence: 99%
“…Gynaecological cancer patients have reported a high level of need for detailed information, information regarding how best to recover from surgery or to avoid recurrence and information regarding physiological and psychological issues [24, 26, 27]. There is evidence that doctors in routine follow-up clinics often fail to identify such problems and, if they do, they fail to address them effectively [28, 29]. …”
Section: Introductionmentioning
confidence: 99%